Pancasila Sebagai Titik Temu Agama-Agama Dan Kemanusiaan: Diskursus Nurcholish Madjid Dan Yudi Latif - Sulbi, Sulbi; Siregar, Salmanul Hakim (Al-Adyan: Journal of Religious Studies, 2021)
Recently, exclusive religious attitudes and disharmony of the humanitarian and political order in differences are getting stronger in Indonesia. This paper aims to analyze the position of Pancasila as the melting pot of religions and the future of humanity. Through literature review; encyclopedias, books, journals, magazines, papers, and media, this paper starts from the data collection, data processing, and data analysis stage. The results of the study show that Indonesia as a pluralist country must create an atmosphere of open dialogue in the spirit of humanity. Therefore, the existence of Pancasila is placed as a bridge meeting point. Not the other way around, understanding the nation and Pancasila in exclusive actions to encourage the behavior to reject the truth of other religions and other people's thoughts. This study concludes that accepting differences gracefully, or acknowledging the existence of other religions is creating the same human order.Akhir-akhir ini, sikap keagamaan eksklusif dan ketidakharmonisan tatanan kemanusiaan maupun politik di tengah perbedaan semakin menguat di Indonesia. Tulisan ini bertujuan untuk menganalisis posisi Pancasila sebagai titik temu agama-agama dan masa depan kemanusiaan. Melalui kajian kepustakaan; ensiklopedi, buku, jurnal, majalah, makalah  dan media-media, tulisan ini dimulai dari pengumpulan data, pengelohan data dan  tahap menganalisis data. Hasil penelitian menunjukan bahwa Indonesia sebagai negara yang pluralis harus menciptakan suasana dialog yang terbuka dalam spirit kemanusiaan. Oleh sebab itu keberadaan Pancasila diletakan sebagai jembatan titik temu. Bukan sebaliknya, memahami bangsa dan Pancasila pada tindakan eksklusif sehingga mendorong pada perilaku menolak kebenaran dari agama-agama lain dan pikiran orang lain. Kajian ini sampai pada kesimpulan bahwa menerima perbedaan dengan lapang dada, atau mengakui keberadaan agama-agama lain adalah menciptakan tatanan kemanusiaan yang sama.